Evaluation of Over-the-Counter Counselling Practices by Libyan Community Pharmacists - Sawsan Alseid; Eman Elmahjoubi; Nabila Rghebi (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objectives: Community pharmacy is a unique hybrid of professionalism and business and dealing with dispensing medicines to outpatient. The pharmacist in community pharmacies plays a crucial role in promoting, maintaining and improving the health of the community; since he/she answers questions about prescription and Over- The- Counter (OTC) drugs and gives advice about home health care supplies and durable medical equipment. Involvement of pharmacists in Over- The- Counter (OTC) counselling will increase the patient ability to understand the risks and benefits of (OTC) drug. The primary aims of this study to assess knowledge, attitudes and perceptions of Libyan community pharmacists and patients toward Over-The-counter (OTC) counselling. Secondary to identify the problems that hinder OTC pharmacy practice. Methods: Two different questionnaires were designed; the first one was distributed to 100 patients and the second designed to pharmacists (n=103) surveyed their knowledge, basic skills, focusing on patients` reasons for visiting community pharmacies and for self-medication. All participants were selected randomly. Results: The results showed that 62% of the community pharmacists assured that they counsel patients before dispensing OTC medication and 59% of them were focused on symptoms and sings of minor ailments. Social and cultural differences among the patients, heavy work load lack of time was the most barriers hindering the pharmacist- patient communication. On the other hand, 29% of pharmacy customers answered that time saving and 11% of them said cost saving were the most reasons for visiting community pharmacies but 8% of them for seeking medication information. Conclusion: The study showed the awareness of Libyan pharmacists towards delivering effective communication skills about OTC was not satisfactory and sufficient knowledge on OTC was still lacking. In addition, the public had negative attitude towards the pharmacists and low expectations from the pharmacy profession. The study recommends a need for training programs for pharmacists in order to nurture the relationships they have with patients.